PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN DAN KOMITE MANAJEMEN RISIKO TERHADAP PENGUNGKAPAN RISIKO PADA PERUSAHAAN PERBANKAN - Mutmainah, Siti; Suryandani, Wulan (Jurnal Manajemen, 2023)
This research was conducted with the aim of testing and proving profitability, company size and risk management committee on risk disclosure in banking companies listed on the Indonesia Stock Exchange in 2016-2021. Total population is 46 companies and only 13 companies are used as the final sample. Data collection techniques using the documentation method. The type of data used is documentary data. The data source is secondary data. The sampling technique used purposive sampling technique. The data analysis technique uses multiple linear regression analysis with the help of IBM SPSS version 25. The results of the research that has been carried out show that profitability has a significant positive effect on risk disclosure, while company size and risk management committee (KMR) have an insignificant positive effect on risk disclosure. The test results of the coeffisient of determination show that the value of Adjusted R2 is 0,803. This means that the variables of proitability, company size and risk magaement committee in the research regression model that has been carried out are able to explain risk disclosure of 80,3%, while 19,7% is explained by other variables not examined in this study.